2020
DOI: 10.1103/physreva.101.012506
|View full text |Cite
|
Sign up to set email alerts
|

Quantum thermodynamics of overdamped modes in local and spatially dispersive materials

Abstract: The quantum thermodynamical properties of (quasi-normal) overdamped electromagnetic modes (eddy currents) are investigated in the context of the magnetic Casimir-Polder interaction. The role of the material response in terms of spatially local and nonlocal material models is discussed. In particular, the focus is set on the system's entropy in the limit of low temperatures. In specific circumstances the spatially local (Drude) model reveals an "entropy defect", while spatial dispersion leads to a more regular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 122 publications
(240 reference statements)
0
30
0
Order By: Relevance
“…On the theoretical side, it was shown that the Lifshitz theory comes into conflict with the Nernst heat theorem when the response of metals with perfect crystal lattices to low-frequency electromagnetic fluctuations is described by the Drude model. This was proven in different geometries for the Casimir interaction between nonmagnetic [44][45][46][47][48] and magnetic [49] metals and, very recently, for the Casimir-Polder interaction of both polarizable and magnetizable atoms interacting with metallic plate [50].…”
Section: Introductionmentioning
confidence: 87%
“…On the theoretical side, it was shown that the Lifshitz theory comes into conflict with the Nernst heat theorem when the response of metals with perfect crystal lattices to low-frequency electromagnetic fluctuations is described by the Drude model. This was proven in different geometries for the Casimir interaction between nonmagnetic [44][45][46][47][48] and magnetic [49] metals and, very recently, for the Casimir-Polder interaction of both polarizable and magnetizable atoms interacting with metallic plate [50].…”
Section: Introductionmentioning
confidence: 87%
“…The only way to formally isolate the local Drude model is the "dirty limit," where τ → 0 at fixedλ p , v F . A discussion of the opposite case, that is typical for low temperatures, is provided by Reiche et al [14], Intravaia et al [26].…”
Section: )mentioning
confidence: 99%
“…The first coincidence is that the typical thermal frequency is quite close to the Drude scattering rate k B T/h = 0.94/τ (gold at room temperature). (For a detailed study of the behaviour of Casimir pressure and entropy at low temperatures, see References [14,26].) The second coincidence is one of length scales.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An example is provided by the analysis of Casimir(-Polder) forces in systems involving spatially nonlocal material and non-trivial geometries beyond the analytically accessible cases. [62,63]. and the other is connected to Landau damping in the bulk,…”
Section: Conclusion and Discussionmentioning
confidence: 99%